Left Ventricular Hypertrophy in Male and Female Judo Athletes - Rossi, Carlo; Roklicer, Roberto; Drid, Patrik; Milovancev, Aleksandra; Trivic, Tatjana; Scardina, Antonino; Carraro, Attilio; Bianco, Antonino (International Journal of Sports Medicine, 2024)
Changes in cardiac geometry develop after intense and prolonged training. Left ventricular enlargement, increased relative wall thickness, and growing mass of the left ventricle occur after strenuous exercise. Combat sports such as judo can lead to left ventricular hypertrophy. Previous studies have found that there are differences in left ventricular chamber size and thickness between the sexes, with female athletes having smaller wall diameters and less hypertrophy than male athletes. The research aims to examine heart muscle adaptations and remodeling of cardiac geometry among elite judo athletes and to evaluate differences between males and females. A cross-sectional study included a group of 19 (males n=10, females n=9) professional judokas between 20 and 30 years. Demographic and anthropometric data were collected. Cardiac geometry was determined by two-dimensional transthoracic echocardiography. In terms of left ventricular mass and the left ventricular mass index significant differences were found between male and female judokas (233.44±68.75 g vs. 164.11±16.59 g, p=0.009), (105.16±24.89 vs. 84.66±15.06, p=0.044), respectively. A greater enlargement of the heart muscle is observed in male athletes compared to the female group. Left ventricle enlargement is likely to occur among elite-level judokas.
Keywords: cardiac remodeling; left ventricular geometry; combat sports; exercise; physical activity; athlete’s heart; martial arts